Evaluasi Kelayakan Instalasi Listrik Rumah Tangga dengan Pemakaian Lebih Dari 15 Tahun Berdasarkan Puil 2000 di Desa Cipaku Kecamatan Cibogo Kabupaten Subang Jawa Barat - Santoso, Dwi Harianto Budi; , Ir. Jatmiko, M.T (2016)
The implementation and execution of electrical regulatory standards determine the quality of the electrical installation, the purpose is that the electrical installation is safe and feasible for use by humans, as stated in the General Terms of electrical installations (PUIL 2000). In this study, there are four factors of reference for a review of parameters, that is: factors grounding resistance, insulation resistance factors, factors conductor cross-sectional area and the installation of a safety factor (MCB). From the research, the data analysis showed the percentage of the feasibility of the grounding resistance factor of 62.5%, insulation resistance factor of 100%, a factor 43.75% Conductor cross-sectional area and the installation of a safety factor (MCB) in terms of his physical condition and function at 100% , So overall lighting installation in Cipaku village, District Cibogo, Subang, West Java 43,75% feasible to use, while 56.25% less worthy to be used. Because according to the criteria of eligibility rate in PUIL 2000, installations every home should reach 100% is considered feasible for use and if the feasibility of installation of each house is less than 100%, it is considered less worthy to be used.